The role of macroeconomic and policy uncertainty in density forecast dispersion - LI, You (Institutional Knowledge at Singapore Management University, 2021)
We explore empirically the role of macroeconomic and policy uncertainty in explaining dispersion in professional forecasters’ density forecasts, and in explaining individual forecaster uncertainty (defined as the uncertainty expressed by individual forecasters in their density forecasts). We focus on US real output growth and inflation, using data from the Philadelphia Fed’s quarterly Survey of Professional Forecasters (SPF), 1992-2016. We find that dispersion in individual density forecasts is related to macroeconomic uncertainty, especially in longer horizon forecasts, but not policy or forecaster uncertainty. There is also little evidence that forecaster uncertainty reflects macroeconomic or policy uncertainty.